THE ROLE of WORKERS’ PARTICIPATION on WORKERS’ WELLBEING, WORKPLACE WELLNESS and SAFETY at SELECTED RESEARCH INSTITUTES in Ilorin, Kwara State, Nigeria - BELLO, Moshood Olalekan; ADAGBOR, Pedro Uwadum; NWANGWU, Adaobi; UKPERE, Wilfred Isioma (Journal of Economic Development, Environment and People, 2022)
Severe consequences of the Covid-19 pandemic reinforced the importance of occupational health and safety. Associated economic disruptions and the entrenchment of institutional dynamics that are at variance with workers’ interests have placed additional pressures on workplace wellness and safety measures. The connection between organisational productivity and worker safety and wellness requires worker participation to institutionalise wellness and safety measures at work. This paper examines the role of workers’ participation in shaping the wellbeing of workers around workplace safety and wellness at two research institutes in Ilorin, Kwara State, Nigeria. A case study design was employed as a research strategy for the study. The justification to adopt this design hinges on its capacity to enhance empirical enquiry on workers’ participation in decisions that affect them as far as workplace wellness and safety are concerned at the case institutes. The samples were selected through a combination of cluster and random sampling methods. A total of 302 questionnaires were distributed at the two research institutions; however, only 265 were returned and found to be appropriate to use in the study. Despite the significance of workplace health and safety awareness, training, education, and regulations, the study showed that employees have not been given the attention that they deserve to shape the programme.